2008
DOI: 10.1096/fj.08-111997
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal and hematological anomalies in HYAL2‐deficient mice: a second type of mucopolysaccharidosis IX?

Abstract: The metabolism of hyaluronan (HA) relies on HA synthases and hyaluronidases, among which hyaluronidase-1 (HYAL1) and -2 (HYAL2) have been proposed as key actors. Congenital HYAL1 deficiency leads to mucopolysaccharidosis IX (MPS IX), a rare lysosomal storage disorder characterized by joint abnormalities. Knowledge of HYAL2 is limited. This protein displays weak in vitro hyaluronidase activity and acts as a receptor for oncogenic ovine retroviruses. We have generated HYAL2-deficient mice through a conditional C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
76
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 90 publications
(81 citation statements)
references
References 42 publications
2
76
0
1
Order By: Relevance
“…27 Similarly, Hyal2-deficient mice have craniofacial anomalies reminiscent of those observed in the two patients we describe. 28 However, Cacna1h-deficient mice have no reported ptosis but rather cardiac fibrosis, which our two patients with CACNA1H homozygous truncation do not have. 29 Interestingly, heterozygous missense changes in CACNA1H have been associated with childhood epilepsy, but the two sisters we describe with a homozygous truncating mutation in this gene are completely normal neurologically except for ptosis.…”
Section: Discussionmentioning
confidence: 56%
“…27 Similarly, Hyal2-deficient mice have craniofacial anomalies reminiscent of those observed in the two patients we describe. 28 However, Cacna1h-deficient mice have no reported ptosis but rather cardiac fibrosis, which our two patients with CACNA1H homozygous truncation do not have. 29 Interestingly, heterozygous missense changes in CACNA1H have been associated with childhood epilepsy, but the two sisters we describe with a homozygous truncating mutation in this gene are completely normal neurologically except for ptosis.…”
Section: Discussionmentioning
confidence: 56%
“…Hyaluronidase Activity-Both cell extracts and media were tested for hyaluronidase activity at different pH levels using zymography, which was performed as recently published by our group (7). In addition, 25-g protein samples from cell extracts were incubated in vitro with 15 g of 2.5 ϫ 10…”
Section: Methodsmentioning
confidence: 99%
“…Mice deficient in each of these genes have recently been described. However, Hyal3 knockout mice do not display a distinct phenotype (5), Hyal1 null animals develop a slowly progressive osteoarthritis without significant elevation of plasma or tissue levels of HA (6), and Hyal2 Ϫ/Ϫ mice show skeletal and hematological anomalies as well as 10-fold increases in plasma HA (7). Some of these apparent anomalies are explained perhaps by the non-enzymatic functions of these proteins.…”
mentioning
confidence: 99%
“…All mice were age matched at adult age, and controls and Hyal-2 KO outbred 129P1.CD1 Hyal2 tm1.1BFla mice 28 (or c57Bl/6 background where indicated) were used. Mice were housed and bred in specific pathogen-free microisolator cages and fed standard Teklad irradiated chow in the Association for Assessment and Accreditation of Laboratory Animal Care Internationale certified Lerner Research Institute Biological Resource Unit.…”
Section: Micementioning
confidence: 99%
“…28,29 Data from our laboratory and others indicate that MKs and platelets contain HA, but little is known about its role in these cells. 30,31 In addition, we found that both mouse and human MKs and platelets contain HYAL2 mRNA and protein with no evidence for HYAL1.…”
mentioning
confidence: 99%